Enhanced Biocompatibility and Antibacterial Activity of Selective Laser Melting Titanium with Zinc-Doped Micro-Nano Topography. (21st May 2019) - Wu, Fan; Xu, Ruogu; Yu, Xiaolin; Yang, Jiamin; Liu, Yun; Ouyang, Jianglin; Zhang, Chunyu; Deng, Feilong
Abstract : Selective laser melting (SLM) titanium is a suitable material for use in customized implants. However, long-term implant survival requires both successful osseointegration and promising antibacterial characteristics. Native SLM titanium thus requires proper modifications to improve its bioactivity and antibacterial efficacy. Micro-arc oxidation (MAO) was conducted on sandblasted SLM substrate to form a microporous TiO2 coating. Subsequently, hydrothermal treatment was applied to fabricate micro-nano zinc-incorporated coatings with different Zn content (1 mM-Zn and 100 μ M-Zn). Surface characterization was performed using scanning electron microscopy, X-ray photoelectron spectroscopy, X-ray diffraction, a three-dimensional profilometer, and a contact angle measuring device. The osteoblast-like cell line MC3T3-E1, Subclone 14, was used in cell viability assays to evaluate adhesion, proliferation, and ALP activity. An antibacterial assay was conducted using Streptococcus sanguinis and Fusobacterium nucleatum . Zn-incorporated samples exhibited higher adhesion, proliferation, and differentiation than did SLM and MAO samples. 100 μ M Zn samples exhibited the highest proliferation, and 1 mM-Zn samples manifested the highest ALP activity. In addition, Zn-incorporated samples exerted inhibitory effects on both Streptococcus sanguinis and Fusobacterium nucleatum . Combining micro-arc oxidation and hydrothermal treatment, we successfully fabricated a novel Zn-incorporated coating on a microporous SLM surface which possesses both outstanding bioactivity and antibacterial efficacy.